Analysis of The Theory of Gold Standard, A Glance on the Book An Introduction to The Theory of Gold Standard: The Monetary System of the New Islamic Civilization - Wahhab Qelich (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The unpleasant effect of Fiat money creation in disruption of economic equilibrium and class division creation is one of the main subjects of expert circles. Therefore, some researchers suggest “Theory of Gold Standard” instead of credit money. The book An Introduction to The Theory of Gold Standard: The Monetary System of the New Islamic Civilization is the most important book in explanation of this theory in Iranian publications. This article deals with the theoretical approach and it reviews the theory of the Gold Standard. The article shows the authors’ valuable concern about the monetary and banking system`s challenges and the unpleasant effects of Fiat money creation. Finally, the book cannot answer ambiguity and main questions scientifically and convincingly. Perhaps simultaneous using of Gold with credit money (no complete removal of credit money) is the more reasonable suggestion for the Iranian monetary system.